Chromosomal defects track tumor subpopulations and change in progression in oligodendroglioma. (16th June 2015) - Nauen, David W; Guajardo, Andrew; Haley, Lisa; Powell, Kerry; Burger, Peter C; Gocke, Christopher D
Abstract: To assess karyotypic changes and tumor subpopulations in progression of oligodendroglioma (ODG) we analyzed histologically diagnosed 1p/19q codeleted cases using single nucleotide polymorphism (SNP) microarray data. We separated cases according to grade, which was assigned blind to karyotype information beyond 1p/19q status. The 51 WHO grade II (O2) and 18 WHO grade III (O3) specimens showed frequent chromosomal locations and patterns of change including loss of heterozygosity (LOH), often copy-neutral, on 9p and LOH on 4p and 4q together. Analysis of co-occurrence indicated that most defects were independent but also suggested increased likelihood of defects on 11q, 13q, and 14q in the presence of defects on 18, 4, and 9, respectively. We used the relative degree of change in B-allele frequency as an indicator of an abnormality's extent, and we present simulated data to clarify how information on subpopulations was thus inferred. Among 9p defects, 89.3% involved the whole tumor, whereas only 47.6% of 4q defects did so. We modeled extent through the tumor as due to a karyotypic change's likelihood of occurring and the fitness it confers on its subpopulation, and used group data to estimate these values. To assess progression directly, we evaluated specimens from six patients who underwent multiple resections since 1996. Four of these patients had received no chemotherapy or radiation, permitting assessment of the natural history of the tumor karyotype in situ . Defects present throughout a tumor at first resection remained so, whereas among subpopulations, some expanded, some remained constant, and some disappeared. The rate of expansion among subpopulations that did so was not uniform, and estimates of fitness predicted subpopulation composition at recurrence. These results extend prior studies of increased karyotypic abnormality in progression of oligodendroglioma and reveal the complex dynamics of subpopulations in the tumor over time. General Scientific Summary: Introduction and background. Cancers are characterized by abnormal growth with reduction of the ability to protect genetic information, so they frequently produce cells with additional gene or chromosome abnormalities. Some of these cells may be more effective at survival and reproduction, allowing relative expansion of their 'subclone'. Oligodendroglioma (ODG), a type of brain cancer, is characterized by deletions of portions of chromosomes 1 and 19, so tissue from suspected cases is often assessed by single nucleotide polymorphism (SNP) array to evaluate chromosomes. SNP data for each chromosome relative to that for 1 and 19 indicates the proportion of tumor involved by each abnormality, and comparison of these subpopulations permits assessment of likelihood of occurring and of competitive advantage. Main results. We analyzed 69 cases of ODG, finding that higher grade tumors had more chromosomal defects in general, and no single change corresponded to higher grade. We developed a simple model for the extent of a given defect through the tumor as a function of its likelihood of occurring and the fitness it confers on its subpopulation, using group data to estimate these values. We then assessed multiple specimens from individual patients, which provide rarely available information on how the tumor evolves over time in the brain. We found that some subpopulations underwent relative expansion, others remained stable, and still others disappeared. In the cases available our model was predictive of tumor composition in recurrence. Wider implications. The study highlights the importance of subpopulations in tumor growth and progression. Any therapy will be more effective against some subclones, so its effect can be viewed as biasing intratumoral competition. This bias will influence tumor response to therapy. Full realization of the potential of personalized medicine for oligodendroglioma and for any cancer will require therapies that account for tumor subpopulations.